Sago and the indigenous peoples of Papua, Indonesia: A review - Fathir Fajar Sidiq; David Coles; Carmen Hubbard; Beth Clark; Lynn J. Frewer (Journal of Agriculture and Applied Biology, 2021)
A significant concern with the food security issue worldwide is indigenous peoples and their food resources. The indigenous peoples of Papua are still very dependent on rice, a heavily imported commodity. During the global pandemic, the indigenous peoples of Papua faced the issue of food supply and food resilience. Simultaneously, Indonesia has the largest sago (Metroxylon sagu Rottb.) palm-growing areas, accounting for over half (51%) of the 2.3 million hectares of sago worldwide, and about 90% of sago is estimated to be in Papua and Maluku. Indigenous food crops such as sago are exceptionally resilient to adverse local environments, highlighting their crucial role in ensuring food and nutrition security, particularly during a natural disaster. However, despite sago’s multiple uses and benefits, it is still poorly evaluated as a food resource by the government, with consumption at relatively low levels. This paper reviews the state-of-the-art regarding indigenous peoples and their food resources, focusing on why sago is essential, not only for the indigenous peoples of Papua but also for the possibility of introducing sago to the world.